Effect of CRTH2 antagonism on the response to experimental rhinovirus infection in asthma: a pilot randomised controlled trial. Issue 10 (29th October 2021) - Farne, Hugo; Glanville, Nicholas; Johnson, Nicholas; Kebadze, Tata; Aniscenko, Julia; Regis, Eteri; Zhu, Jie; Trujillo-Torralbo, Maria-Belen; Kon, Onn Min; Mallia, Patrick; Prevost, A Toby; Edwards, Michael R; et al.
Abstract : Background and aims: The chemoattractant receptor-homologous molecule expressed on T helper type 2 cells (CRTH2) antagonist timapiprant improved lung function and asthma control in a phase 2 study, with evidence suggesting reduced exacerbations. We aimed to assess whether timapiprant attenuated or prevented asthma exacerbations induced by experimental rhinovirus (RV) infection. We furthermore hypothesised that timapiprant would dampen RV-induced type 2 inflammation and consequently improve antiviral immune responses. Methods: Atopic patients with partially controlled asthma on maintenance inhaled corticosteroids were randomised to timapiprant (n=22) or placebo (n=22) and challenged with RV-A16 3 weeks later. The primary endpoint was the cumulative lower respiratory symptom score over the 14 days post infection. Upper respiratory symptoms, spirometry, airway hyperresponsiveness, exhaled nitric oxide, RV-A16 virus load and soluble mediators in upper and lower airways samples, and CRTH2 staining in bronchial biopsies were additionally assessed before and during RV-A16 infection. Results: Six subjects discontinued the study and eight were not infected; outcomes were assessed in 16 timapiprant-treated and 14 placebo-treated, successfully infected subjects. There were no differences between treatment groups in clinical exacerbation severity including cumulative lower respiratory symptom score day 0–14 (difference 3.0 (95% CI −29.0 to 17.0), p=0.78), virus load, antiviral immune responses, or RV-A16-induced airway inflammation other than in the bronchial biopsies, where CRTH2 staining was increased during RV-A16 infection in the placebo-treated but not the timapiprant-treated group. Timapiprant had a favourable safety profile, with no deaths, serious adverse events or drug-related withdrawals. Conclusion: Timapiprant treatment had little impact on the clinicopathological changes induced by RV-A16 infection in partially controlled asthma.